From Independence to Involvement: The Case Study of Politeness Strategy in Chinese-English Business Interpreting - Jiaqi Xue (Media and Intercultural Communication: A Multidisciplinary Journal)
The article examines the utilization of politeness strategies in a Chinese-English business interpreting. With the independence politeness strategy and involvement politeness strategy as frameworks, a case study was carried out to analyze the politeness strategies employed by an interpreter in a Chinese-English business interpreting scenario. The results of the study indicate that the interpreter tends to transition from the independence politeness strategy in the source text to the involvement politeness strategy in the target text. More specifically, the interpreter appears to convert the independence politeness strategy employed by the Chinese speaker into the involvement politeness strategy in the English rendering. Furthermore, it is suggested that the interpreter’s manipulation might be deemed acceptable based on the type of rendering and the purpose of interpreting. Overall, this study can not only shed light on the usage of politeness strategy in intercultural business negotiation interpreting, but also expand the application of politeness strategy in interpreting studies. It also provides some practical implications for the politeness strategies employed in intercultural communication.